How does aging affect the types of error made in a visual short-term memory ‘object-recall’ task? - Sapkota, Raju P.; Linde, Ian van der; Pardhan, Shahina (Frontiers in Aging Neuroscience, 2015)
This study examines how normal aging affects the occurrence of different types of incorrect responses in a visual short-term memory object-recall task. Seventeen young (Mean = 23.3 years, SD = 3.76), and 17 normally aging older (Mean = 66.5 years, SD = 6.30) adults participated. Memory stimuli comprised 2 or 4 real world objects (the memory load) presented sequentially, each for 650ms, at random locations on a computer screen. After a 1000ms retention interval, a test display was presented, comprising an empty box at one of the previously presented 2 or 4 memory stimulus locations. Participants were asked to report the name of the object presented at the cued location. Errors rates wherein participants reported the names of objects that had been presented in the memory display but not at the cued location (non-target errors) vs. objects that had not been presented at all in the memory display (non-memory errors) were compared. Significant effects of aging, memory load and target recency on error type and absolute error rates were found. Non-target error rate was higher than non-memory error rate in both age groups, indicating that VSTM may have been more often than not populated with partial traces of previously presented items. At high memory load, non-memory error rate was higher in young participants (compared to older participants) when the memory target had been presented at the earliest temporal position. However, non-target error rates exhibited a reversed trend, i.e., greater error rates were found in older participants when the memory target had been presented at the two most recent temporal positions. Data are interpreted in terms of proactive interference (earlier examined non-target items interfering with more recent items), false memories (non-memory items which have a categorical relationship to presented items, interfering with memory targets), slot and flexible resource models, and spatial coding deficits.